2000
DOI: 10.1046/j.1440-1819.2000.00637.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of telepsychiatry: A preliminary study

Abstract: Telemedicine is the provision of professional medical services from sites removed from the patient. This study was conducted in order to assess the reliability of psychiatric evaluations via video-consultation. The inter-rater reliability was determined for each interviewing condition by employing the reliability-testing paradigm in which the brief psychiatric rating scale (BPRS) and the interclass correlation coefficient (ICC) are used. The inter-rater reliability scores between face-to-face interviews and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Research overall suggests that videoconferencing is a reliable and feasible method of assessing patients with psychiatric illness (33); however, most of these studies are limited in having small numbers of participants. In the 1970’s, Dwyer and colleagues (34) used a microwave bidirectional television to provide a range of services which included diagnostic interviews, pharmacotherapy, crisis management, as well as long-term therapy for patients with psychoses and personality disorders.…”
Section: Resultsmentioning
confidence: 99%
“…Research overall suggests that videoconferencing is a reliable and feasible method of assessing patients with psychiatric illness (33); however, most of these studies are limited in having small numbers of participants. In the 1970’s, Dwyer and colleagues (34) used a microwave bidirectional television to provide a range of services which included diagnostic interviews, pharmacotherapy, crisis management, as well as long-term therapy for patients with psychoses and personality disorders.…”
Section: Resultsmentioning
confidence: 99%
“…Common limitations in the systematic reviews were: grading of the evidence was not evident in the recommendations; studies were assessed for quality but were not linked to recommendations; all of the systematic reviews reported on the same 10 RCTs; 6,58-66 two child and adolescent RCTs [67][68] and two of the systematic reviews 23,39 included information from a further 8 moderate quality control studies. [69][70][71][72][73][74][75][76] The systematic reviews also only included studies up until 2008. The authors identified a further four RCTs published post 2008 which showed similar evidence to the studies in the systematic reviews.…”
Section: Resultsmentioning
confidence: 99%
“…For example, two studies assessed reliability estimates between telepsychiatry conducted with varying levels of bandwidth to determine if connection quality impacted reliability. One report observed ICCs greater than 0.95 across all conditions of varying bandwidth quality among two psychiatrists rating eight psychiatric outpatients and nine health controls using the BPRS [74] . On the other hand, Yoshino et al [75] observed statistically significantly lower ICC scores in the narrow bandwidth condition compared to the broad bandwidth in for BPRS scores.…”
Section: Hubley S Et Al Telepsychiatry Reviewmentioning
confidence: 99%